Age Trajectories of Perceptual Speed and Loneliness: Separating Between-Person and Within-Person Associations. (9th November 2021) - Drewelies, Johanna; Windsor, Tim D; Duezel, Sandra; Demuth, Ilja; Wagner, Gert G; Lindenberger, Ulman; Gerstorf, Denis; Ghisletta, Paolo
Abstract: Objectives: We aimed at examining between-person and within-person associations across age trajectories of perceptual speed and loneliness in old age. Method: We applied multilevel models to 4 waves of data collected over 6 years from 1, 491 participants of the Berlin Aging Study II (60–88 years at baseline, 50% women) to disentangle between-person and within-person associations across age trajectories of perceptual speed and both emotional and social loneliness. Sex and education were considered as relevant individual characteristics and included as covariates in the model. Results: Analyses revealed that on average perceptual speed exhibited moderate within-person age-related declines, whereas facets of loneliness were rather stable. Perceptual speed did not predict age trajectories of emotional or social loneliness, at either the between- or within-person level. In contrast, loneliness discriminated individuals at the between-person level, such that those feeling emotionally or socially more lonely showed lower cognitive performance than those feeling emotionally or socially less lonely. Predictive effects of social loneliness were stronger for relatively young people (i.e., in their mid to late 60s) than for relatively older participants (i.e., in their 80s). In addition, predictive effects of social loneliness for perceptual speed at the within-person level were modest and deviated in direction and size from between-person social loneliness effects among those in their mid- to late 60s, whereas they did not among those in their 80s. Discussion: We conclude that loneliness may serve as a precursor for basic cognitive functioning in old age and suggest routes for further inquiry.